Bimodal expression of RHOH during myelomonocytic differentiation: Implications for the expansion of AML differentiation therapy. Issue 2 (20th January 2021) - Galiègue‐Zouitina, Sylvie; Fu, Qiangwei; Carton‐Latreche, Céline; Poret, Nicolas; Cheok, Meyling; Leprêtre, Frédéric; Figeac, Martin; Quesnel, Bruno; El Bouazzati, Hassiba; Shelley, Carl S
Abstract: RhoH is an unusual member of the Rho family of small GTP‐binding proteins in that it lacks GTPase activity. Since the RhoH protein is constantly bound by GTP, it is constitutively active and controlled predominantly by changes in quantitative expression. Abnormal levels of RHOH gene transcripts have been linked to a range of malignancies including acute myeloid leukemia (AML). One of the hallmarks of AML is a block in the normal program of myeloid differentiation. Here we investigate how myeloid differentiation is controlled by the quantitative expression of RHOH . Our analysis demonstrates that increasingly mature myeloid cells express progressively lower levels of RHOH . However, as monocytic myeloid cells terminally differentiate into macrophages, RHOH expression is up‐regulated. This up‐regulation is not apparent in AML where myeloid differentiation is blocked at stages of low RHOH expression. Nevertheless, when the up‐regulation of RHOH is forced, then terminal macrophage differentiation is induced and the Cdc42 and Wnt intracellular signalling pathways are repressed. These results indicate that RHOH induction is a driver of terminal differentiation and might represent a means of effecting AML differentiation therapy. The potential of this therapeutic strategy is supported by forced up‐regulation of RHOH reducing the ability of AML cells to produce tumours in vivo .